Stent implantation in severe aortic coarctation in a pediatric patient with Turner syndrome: Case report and literature review - Lin, Yuese; Zhu, Ling; Li, Xuandi; Ba, Hongjun; He, Xiufang; Li, Shujuan (Frontiers in Pediatrics, 2023)
Background: Turner syndrome is a rare systemic disease and quite a proportion of these patients would suffer from aortic coarctation. Selection of optimal therapy for aortic coarctation in patients with Turner syndrome is difficult due to the pathologic change of systemic vessel. Case Presentation:We report one successful case of covered stent implantation for treatment of severe native coarctation of the aorta in a 15-year-old 36kg patient with Turner syndrome.A covered stent was implanted in this patient. After stent implantation, peak systolic pressure gradient immediately decreased from 48 to 14 mmHg. Aortic diameter at coarctation site increased from 3 to 10 mm after stenting. Femoral arterial complication occured in this case,and we stablized the situation finally. Results: During a follow-up of 3 years, no restenosis of aortic coarctation was observed and the patient no longer suffered from hypertension. Dissection of the right femoral artery remained stable. Conclusion:Covered stent implantation for severe aortic coarctation in patients with Turner syndrome could be safe and effective. But it needs to be very cautious of using the technique to prevent complication.